Dos "dividendos da paz" à guerra contra o terror: Gastos militares mundiais nas duas décadas após o fim da guerra fria - 1991-2009 - Edison Benedito da Silva Filho; Rodrigo Fracalossi de Moraes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This article examines the world military expenditures in the period 1991-2009, based on an exploratory analysis about the institutional and economic factors that affected the defense budgets in the countries with the largest military expenditures in the world. Furthermore, there is a comparative analysis of the composition of military expenditures in Brazil and North Atlantic Treaty Organization (NATO) countries in the 2000s, expounding differences on the proportions of resources allocated for weapons purchases and payment of personnel. Finally, the article analyzes the different degrees of investments on capital intensity in these countries' militaries, stressing their differences in comparison with the United States.
Keywords: H56; 330; military expenditures; 1990s; 2000s; expenditures on military weapons; expenditures on military personnel; military's capital intensity; Militärausgaben; Brasilien; Welt